Prenatal Phenol and Paraben Exposures and Adverse Birth Outcomes: A Prospective Analysis of U.S. Births - Leonardo Trasande; Morgan E. Nelson; Akram Alshawabkeh; Emily S. Barrett; Jessie P. Buckley; Dana Dabelea; Anne L. Dunlop; Julie B. Herbstman; John D. Meeker; Mrudula Naidu; Craig Newschaffer; Amy M. Padula; et al. (Environment International, 2024)
Background: Synthetic chemicals are increasingly being recognized for potential independent contributions to preterm birth (PTB) and low birth weight (LBW). Bisphenols, parabens, and triclosan are consumer product chemicals that act via similar mechanisms including estrogen, androgen, and thyroid disruption and oxidative stress. Multiple cohort studies have endeavored to examine effects on birth outcomes, and systematic reviews have been limited due to measurement of 1–2 spot samples during pregnancy and limited diversity of populations. Objective: To study the effects of prenatal phenols and parabens on birth size and gestational age (GA) in 3,619 mother-infant pairs from 11 cohorts in the NIH Environmental influences on Child Health Outcomes program. Results: While many associations were modest and statistically imprecise, a 1-unit increase in log10 pregnancy averaged concentration of benzophenone-3 and methylparaben were associated with decreases in birthweight, birthweight adjusted for gestational age and SGA. Increases in the odds of being SGA were 29% (95% CI: 5%, 58%) and 32% (95% CI: 3%, 70%), respectively. Bisphenol S in third trimester was also associated with SGA (OR 1.52, 95% CI 1.08, 2.13). Associations of benzophenone-3 and methylparaben with PTB and LBW were null. In addition, a 1-unit increase in log10 pregnancy averaged concentration of 2,4-dichlorophenol was associated with 43% lower (95% CI: −67%, −2%) odds of low birthweight; the direction of effect was the same for the highly correlated 2,5-dichlorophenol, but with a smaller magnitude (-29%, 95% CI: −53%, 8%). Discussion: In a large and diverse sample generally representative of the United States, benzophenone-3 and methylparaben were associated with lower birthweight as well as birthweight adjusted for gestational age and higher odds of SGA, while 2,4-dichlorophenol. These associations with smaller size at birth are concerning in light of the known consequences of intrauterine growth restriction for multiple important health outcomes emerging later in life.